Prevalence and risk factors of subjective cognitive decline in older adults in Baotou, China: a cross-sectional study - Ma, Shang-Jia; Yu, Yan-Xue; Tian, Kai; Yong, Wen; Yu, Wen-Long; Bai, Ru-Yu; Wu, Li-E; Guo, Xia (Frontiers in Aging Neuroscience, 2024)
Objectives: Subjective cognitive decline (SCD) as a stage between healthy cognition and early neurocognitive disorders, has been proposed to be helpful in the diagnosis of prodromal neurocognitive disorders. To investigate the prevalence of SCD and the related risk factors on the prevalence.A cross-sectional study involving 1120 elderly subjects residing in Baotou, China. From June 2022 to June 2023, the data were gathered by research assistants with training utilizing standardized questionnaires. The following factors were evaluated: subjective cognitive decline, physical and cognitive activity levels, past medical history, demographics, instrumental activities of daily living, and cognitive function. Risk factors of SCD were estimated multivariate logistic and linear regression analyses.The prevalence of SCD was 43.8%. Permanent residence, marital status, BMI, dietary habits, average sleep duration per night, smoking, diabetes, coronary heart disease, and visual impairment were significantly associated with SCD (p <0 .05). Multivariable logistic regression analysis showed obesity, vegetarian-based, smoking for a long time, diabetes and coronary heart disease, visual impairment, no spouse, and average sleep duration per night < 6h were independent risk factors for SCD. Based on the gender analysis, the difference in marital status, dietary habits, average sleep duration per night, smoking, drinking, and hypertension was statistically significant (p<0.001). Conclusions: The prevalence of subjective cognitive decline was high among elder adults. We discovered significant differences in the prevalence or risk factors for SCD between men and women based on their sex. This study provides a more theoretical basis for the early prevention and screening of cognitive impairment diseases in the elderly population.